Investigation of Health Literacy Status in Beijing, China - Jianhui Shi; Li Qi; Yuqing Li; Xiurong Liu (SLACK Incorporated, 2020)
Background: The Chinese government uses health literacy as an evaluation to estimate population health status in national strategic planning. A health literacy survey system for the city of Beijing, China was established in 2012 with triennial surveys to obtain representative data for the whole city. Objective: The objective of this study was to examine results of the 2015 Beijing Health Literacy Survey and to identify population subgroups that may warrant intervention due to high risk for not having adequate health literacy. Methods: This was a cross-sectional study in which participants were selected by multistage stratified cluster sampling. The information was collected in 2015 in face-to-face interviews on the Chinese Citizen Health Literacy Questionnaire. A total of 12,876 interviews were included in the final analyses. Weighting was conducted in all statistical analyses to obtain representative estimates, and multiple logistic regression was applied to examine the independent influencing factors on health literacy level (adequate/inadequate). Key Results: Overall, 28% of participants had adequate health literacy. Urban residents had a higher proportion of participants with adequate health literacy compared to rural residents (29.5% vs. 19%, p < .01). Women (29.7%) had a higher proportion of participants with adequate health literacy compared to men (29.7% vs. 26.4%, p < .01). The proportion of participants with adequate health literacy was significantly different among age groups (χ2 = 332.9, p < .01). Residents age 25 to 34 years had the highest rate of adequate health literacy (33.9%). The proportion of participants with adequate health literacy increased as participants obtained more education (χ2 = 818.4, p < .01). Residents in households with higher income had a higher rate of adequate health literacy (χ2 = 462.4, p < .01). Gender, age, education, and household income were independently associated with the level of health literacy. Conclusions: Substantial variation exists in health literacy level among age groups, gender groups, and education groups. Taking these disparities into account is important when developing health policies and allocating resources.